A beszerzési logisztika folyamatainak elemzése - Skaper Dorina (2021)
In my present dissertation I have set the analysis of the procurement logistics processes of a specified company. The effective functioning of an economic company requires the more effective implementation of procurement. This activity is the basis for multi-commercially used process, thereby requiring a sufficient amount of time spending, as it can easily inter-rupt a possible procedure. The purpose of my dissertation is to determine the possible problems encountered in the performance of this process by using and using a lengthy analysis. I have associated the difficulties currently in place to be accomplished, to which I have assigned a proposal as an option. Among the points needed to implement the process, we also find that the company performs properly and has not occurred in this connection. The purchasing used thus owns beneficial and disadvantages in a nearly identical manner. I used several research opportunities to meet the analysis. Primary literature on the topic of procurement prevailed while writing the dissertation. I projected the definitions in the literature to the mode used in the company, thereby a benchmark for a benchmark. With personal interviewing, I measured the position represented by corporate workers from the current corporate system and the aspects of the need for acquisition of the need for purchase and how the procurement demand is made to the logistic. Compared to the proceeding of the order used in the past against the current system, so I could turn it down, what changes and improvements occurred recently. The most important results in the research include the lack of specifications, as the-re is no need for any information necessary for the purchaser. By providing adequate amounts of information, it is possible to increase targeting work. The lack of administra-tion is reflected in the company, which makes it difficult to implement effective imple-mentation. Several employees do not apply the integrated corporate governance system, prefer the traditional, faster solution. Overall, it can be said that the company seeks to maximize the elements and points needed to carry out the procurement process. Each task is performed properly by complying with the required requirements, yet I met several outstanding problems. My suggestion is to have different trainings. By retaining discussions, we increase the size of intra-corporate communication. It is important to take advantage of the available options for workers, as it can only eliminate the excessive increase in the emerging problems